Repercussões da COVID-19 na assistência odontológica das Equipes de Saúde Bucal em dois municípios do Cariri cearense - Silva, Micael Sampaio da (Universidade Federal de São Carlos, 2024)
Investigating the care and work practices of dental surgeons in the face of the COVID-19 pandemic has made it possible to assess the risks and understand dental care experiences in a challenging context, contributing to management and health education decisions based on evidence and situational singularities. Thus, the objective was to identify and analyze the repercussions of COVID-19 on dental care provided by dental surgeons from the Oral Health Teams (ESB) of the Unified Health System (SUS) in the municipalities of Crato and Barbalha, located in the south of the state of Ceará, with a focus on the quality of services and the safety of patients and health professionals. This is a descriptive empirical study with an objective and practical dimension, with a quantitative-qualitative cross-sectional approach, which involved 30 dental surgeons and was carried out between April and June 2023. For data collection, an online form was used from the Google Forms platform (Google Corp.) with objective and subjective questions to which participants reported their practical experiences related to their work during the COVID-19 pandemic. The results showed a reduction in dental care, accepted by 93.3% of dentists, and a change in the oral health practices of these professionals, prioritizing activities that did not generate aerosols in dental environments. On the other hand, the reorganization of care resulted in discontent on the part of dental service users due to the impossibility of carrying out elective procedures, producing a care gap. The lack of Personal Protective Equipment (PPE), the unavailability of materials and instruments and the persistence of health managers to increase the number of appointments were challenges faced by the ESB. Therefore, this research supports the design and development of strategies and actions to improve the infrastructure of dental care as a requirement to guarantee the quality of services and the safety of professionals and patients. It will also serve as the basis for the creation of a technical product, a manual of good biosafety practices for dental clinics.
Repercussions of COVID-19 on dental care of oral health teams in two municipalities in Cariri cearense
Repercusiones del COVID-19 en la atención odontológica de los equipos de salud bucodental en dos municipios del Cariri cearense
Keywords: Odontologia; COVID-19; Atenção à saúde; Sistema único de saúde; Gestão em saúde; Dentistry; COVID-19; Delivery of health care; Unified health system; Health management; CIENCIAS DA SAUDE::ODONTOLOGIA; CIENCIAS DA SAUDE::SAUDE COLETIVA; CIENCIAS DA SAUDE; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA